PERBEDAAN TINGKAT KECEMASAN ANTARA IBU HAMIL PRIMIGRAVIDA DAN MULTIGRAVIDA DIRUMAH SAKIT BUDI KEMULIAAN KOTA BATAM - Cevy Amelia; Sarmini Sarmini (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Background:Pregnancy is a mandatory process in order to obtain offspring. Third trimester is considered when pregnancy reached 28-36 weeks. During this third trimester, pregnant women are usually divided into two types, i.e. primigravida and multigravida. Anxiety is often found in pregnant women in their third trimester. Primigravid women usually shows more anxiety compared to multigravid women.Methods:The method of this study was observational analytic using cross sectional design. The sampling technique used was accidental sampling using a total sample of 70 people.Results:This study consisted of 70 participants (100%) with 35 primigravidas and 35 multigravidas. The anxiety percentage of primigravid women consisted of 20 people (28%) with mild anxiety, 20 people (58%) with moderate anxiety, and 5 people (14%) with severe anxiety. The anxiety percentage of multigravida women consisted of 22 people (62%) with mild anxiety, 11 people (32%) with moderate anxiety, and 2 people (6%) with severe anxiety. The results of statistical test showed p value = 0.005, which means that there was a difference of anxiety level between primigravid and multigravida women in their third trimester in Budi Kemuliaan Hospital, Batam. Conclusion:This study concludes that there was a difference of anxiety level between primigravid and multigravida women in their third trimester in Budi Kemuliaan Hospital, Batam.